Cardio-Nephrology : Confluence of the Heart and Kidney in Clinical Practice - Rangaswami, Janani; Lerma, Edgar V.; Ronco, Claudio (Springer International Publishing : Imprint: Springer, 2017)
Extending from the outpatient management of cardiovascular and kidney disease, to hospital-based decision making in patients with cardio-renal disease and complex interfaces such as hemodialysis in patients with ventricular assist device support, this book serves as a single reference point for cardiology and nephrology clinicians and researchers dealing with the significant overlap areas between these two specialties. Chapters cover the physiology, biomarkers, therapeutic agents and full spectrum of these comorbidities and feature separate sections on cardiovascular and CKD evaluations, stratification of kidney transplant patients, lipid management in CKD, interventional strategies and hypertension. Leaders in cardiology, nephrology, hypertension and lipidology bring together the latest evidence with their collective clinical experience into this invaluable resource.This textbook is an essential resource for physicians and allied professionals practicing cardiology, nephrology, students and physician trainees, to deepen their understanding of this crucial field.
Keywords: Medicine.; Critical care medicine.; Cardiology.; Nephrology.; elektronické knihy; electronic books